1988
DOI: 10.1038/bjc.1988.177
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the anti-tumour effect of melphalan by the vasoactive agent, hydralazine

Abstract: Summary The vaso-active drug hydralazine causes a considerable increase in the cytotoxic effect of melphalan towards the KHT tumour in mice. The enhancement in response, measured as the concentration of melphalan required to achieve a given tumour response, is 3.0 and 2.35 when determined using the regrowth delay assay and the technique for determining surviving fraction in vitro following treatment in vivo respectively. In contrast, measurement of systemic toxicity shows that the addition of hydralazine only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…This resistance has been attributed to the 'steal' phenomenon, whereby tumour perfusion is decreased when blood flow to other tissues is increased. Induction of severe hypoxia in tumours can greatly increase the effect of bioreductive agents [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This resistance has been attributed to the 'steal' phenomenon, whereby tumour perfusion is decreased when blood flow to other tissues is increased. Induction of severe hypoxia in tumours can greatly increase the effect of bioreductive agents [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have shown that administering the vasoactive drug hydralazine after melphalan treatment can enhance the antitumour efficacy of this chemotherapeutic agent (Stratford et al, 1987(Stratford et al, , 1988Chaplin et al, 1989). Consequently, this was the first chemotherapeutic agent evaluated in the present studies.…”
Section: Resultsmentioning
confidence: 79%
“…The use of post-treatment hydralazine exposure has not, however, been restricted to the combination with bioreductive drugs. In addition, this treatment strategy has been shown to yield effective enhancement of selected chemotherapeutic agents and hyperthermia (Chaplin, 1987;Stratford et al, 1988 (Brown, 1982;McNally, 1982;Siemann, 1982Siemann, , 1984. Further, the majority of these investigations implicate hypoxia as a requirement for the expression of chemosensitisation (Siemann, 1984;Siemann & Mulcahy, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Horsman et al (1996) have shown that tumour blood flow changes brought about by nitro-L-arginine lasted no more than an hour, whereas the changes in redox status reported by Wood et al (1994a) could last for up to 6 h. Thus, the underlying mechanism mediating these anti-tumour effects is likely to be a complex interaction between hypoxia induction and entrapment (distribution and pharmacokinetics). Such interactions have been shown to contribute to the potentiation of the activity of both RSU1069 and the alkylating agent melphalan using a variety of techniques for modifying blood flow to tumours (Chaplin and Acker 1987;Stratford et al, 1988;Bremner et al, 1990;Castellino et al, 1995).…”
Section: Discussionmentioning
confidence: 99%